2008
DOI: 10.1021/cm702338h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Symmetry, and Physical Properties of Cerium Pyrophosphate

Abstract: CeP 2 O 7 , a close structural relative of ZrP 2 O 7 , and many other M IV X 2 O 7 (X -P, V, As) phases, forms on heating Ce(HPO 4 ) 2 • xH 2 O between ∼300 and 600 °C and decomposes by oxygen loss at higher temperatures. In-situ X-ray diffraction measurements showed, for some precursor batches, the formation of CeP 2 O 7 in two distinct stages. At room temperature, CeP 2 O 7 is pseudocubic, but probably triclinic, displaying positive thermal expansion below ∼115 °C. Above this temperature, there is a transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…High pressure studies in the ZrV 2 O 7 family have been limited to TiP 2 O 7 , ZrP 2 O 7 , CeP 2 O 7 , ZrV 2 O 7 and HfV 2 O 7 [103,111,112,113,114]. Interestingly, in situ diffraction experiments show no evidence for pressure-induced phase transitions or amorphization for TiP 2 O 7 and ZrP 2 O 7 , both of which are positive thermal expansion compounds.…”
Section: Negative Thermal Expansion Due To Transverse Vibrationsmentioning
confidence: 99%
“…High pressure studies in the ZrV 2 O 7 family have been limited to TiP 2 O 7 , ZrP 2 O 7 , CeP 2 O 7 , ZrV 2 O 7 and HfV 2 O 7 [103,111,112,113,114]. Interestingly, in situ diffraction experiments show no evidence for pressure-induced phase transitions or amorphization for TiP 2 O 7 and ZrP 2 O 7 , both of which are positive thermal expansion compounds.…”
Section: Negative Thermal Expansion Due To Transverse Vibrationsmentioning
confidence: 99%
“…Only a conventional calcination technique has been used to prepare CeP 2 O 7 and Ce(PO 3 ) 4 in previous studies [3,7,8,15,[29][30][31] 4 were adequately mixed in an agate mortar. The mixture was stored in a porcelain crucible with an insulation layer and directly irradiated at various MW powers for different times.…”
Section: ) On U(vi)mentioning
confidence: 99%
“…In recent years, considerable attention has been paid to rare earth phosphates because of their applications in novel functional materials, such as fluorescence materials [1,2], proton conductors [3][4][5][6], catalysts [7][8][9][10], magnetic cooling material [11], sunscreen materials [12][13][14], negative thermal expansion materials [15,16], and efficient adsorbents for radwaste [17][18][19]. Several phosphates such as Zr 2 O(PO 4 ) 2 , ZrP 2 O 7 and Th 4 (PO 4 ) 4 P 2 O 7 have been studied as potential substitutes for immobilization and long-term storage of uranium [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the cerium pyrophosphates are thermally unstable at 4400 1C and therefore their sintering at the higher temperature is avoided [10,11], it has been observed that they give fairly dense specimens even on sintering at temperatures $ 400 1C [5,[8][9][10][11]. Considering the fact that pyrophosphates of cerium and tin are generally isomorphous, with both having cubic lattice and Pa3 space group [12,13], it is expected that on partially replacing Sn 4 þ ion in SnP 2 O 7 by Ce 4 þ ion, Ce 4 þ ion would be easily incorporated into tin pyrophosphate lattice, although the ionic radius of Ce 4 þ ion (r=0.87 Å) is larger than that of Sn 4 þ ion (r=0.69 Å) [14], and improve the sinterability of tin pyrophosphate. Therefore, in this work, we have doped tin pyrophosphate with (0-10%) CeO 2 and analyzed its effect on the phase composition, sinterability and microstructure, and ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%